Influência do suporte e método de preparação na atividade de catalisadores para reforma de etanol com vapor d'água - Silva, Fernando Alves da (2014)
Hydrogen production from sources that contain in their molecular matrix (hydrocarbons and alcohols) to use in fuel cells has intensified the search for active and selective catalysts for the conversion to H2. Copper and nickel based in different supports has shown promise for it. Zeolites, niobium and silica were evaluated in the ethanol steam reforming to produce hydrogen energy. The reaction routes were strongly dependent on the type of support; catalysts prepared by ion exchange (zeolites and niobic acid) have low yield for this reaction, resulting in partial oxidation of alcohol. For the impregnation method, niobium and silica support had ensured high conversion and selectivity to H2, with low by-product distribution and absence of dehydration products, also for coprecipitation. The formation of compounds between active phase and support, observed by XRD and RTP-H2 suggests that niobium not only acts as support in this reaction. In these cases, the higher water feed concentration favors the conversion of ethanol and by-products (from dehydrogenation and decomposition) to hydrogen, which was also observed with increasing catalyst mass. At 450 °C, the selectivity system achieves near stoichiometric and complete conversion of ethanol.